Instability of Property Sector Stock Return Period 2014 – 2021 - Fazri, Muhammad; Widhiastuti, Rosalia Nansih; Kisman, Zainul (Archives of Business Research, 2023)
This study aims to determine the effect of exchange rates, dividend payout ratios, net profit margins, earnings per share, and current ratios on stock returns in the property and real estate sub-sectors listed on the IDX for the 2014-2021 period. This study uses secondary data. The population of this study consists of property and real estate sub-sector companies listed on the IDX during the 2014-2021 period. The sample used in this study consisted of property and real estate sub-sector companies with complete data during the study period. The analytical method used is panel data regression analysis, with the analysis tool using E-views 12 software. The results show that partially the exchange rate has a significant negative effect on stock returns, while the dividend payout ratio, net profit margin, earnings per share, and current ratio do not affect stock returns. Taken together, the exchange rate, dividend payout ratio, net profit margin, earnings per share, and current ratio have a significant influence on stock returns in the property and real estate sub-sector companies listed on the IDX for the 2014-2021 period.